Bantuan Dana Bank Dunia Dalam Perspektif Pemenuhan Hak-hak Ekosob: Studi Kasus Pada Sektor Pendidikan di Indonesia - Satria Unggul Wicaksana Prakasa (Universitas Serang Raya, 2018)
The World Bank assistance in the education sector in Indonesia as a developing country faced with an interest in the fulfillment of the right to education in the perspective of Economy, Social, and Culture (ESC) rights for the society. For Indonesia, World Bank assitance must be in line with the national regulation, therefore harmonization into national law is necessary. The World Bank assistance is aimed at accelerating free trade, and the achievement of global education standards for the recipient countries. Thus, the alignment of the education sector with the interests of the economy and the free market may threaten the education rights of Indonesian citizen. This article will focus on the fulfillment of education right in Indonesia. Seeing the facts from the background, the formulation of the problems raised in this legal research are: (1). characteristics of educational assistance by the World Bank for developing countries. (2). Compatibility between World Bank assistance standards with the fulfillment of ESC rights in education in Indonesia. The purpose of this research is to analyze the characteristics of educational assistance by the World Bank for the third world countries and the suitability of the World Bank assistance to the fulfillment of ESC rights in education in Indonesia. This article based on the normative legal research method, and employs the statute and conceptual approach. It is found two results. First, the World Bank assistance to the education sector has been implemented in several countries, including Indonesia. The fulfillment of the right to education in developing countries have been experiencing an intervention and support from the World Bank. The World Bank asisstence is aim at achieving the goal of education, and to ensure the aid has been allocated for education projects, and to provide students with global education standards. Second, by employing the SABER standard with 4-a method to measure the suitability of the World Bank assistance in the fulfillment of the right to education in Indonesia, it is found that there remain a problem in the ‘acceptability’ standard. The World Bank should give more weights to the local wisdoms when providing asisstence in the recipient country.